A companion to the English novel - Arata, Stephen; Haley, Madigan; Hunter, J. Paul, 1934-; Wicke, Jennifer (Hoboken : Wiley-Blackwell, 2015)
"Explores the history, evolution, genres, and narrative elements of the English novel, while chronicling its development from the early 18th century to the present day"--
Part I. The novel and its histories -- Part II. The novel and its genres -- Part III. The novel in pieces -- Part IV. The novel in theory -- Part V. The novel in circulation -- Part VI. Geographies of the novel -- Part VII. The novel, public and private.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: English fiction -- History and criticism; Literary form -- History; Fiction -- Technique -- History; Narration (Rhetoric) -- History; Authors and readers -- Great Britain -- History; LITERARY CRITICISM / General; Authors and readers; English fiction; Fiction -- Technique; Literary form; Narration (Rhetoric); Great Britain; Criticism, interpretation, etc; History; Electronic books